KONTRIBUSI EPISTEMOLOGIS FĀḌIL AL-SĀMARĀ'Ī DALAM ILMU BALAGHAH: STUDI KONSEPTUAL TENTANG TEORI TAQDĪM-TA'KHĪR AL-QUR'ANI - Muhammad Ivang Rizaldi; HD Hidayat; Zainal Muttaqin (Universitas Islam Negeri Palopo, 2026)
This paper examines the syntactic flexibility of Arabic, which allows for variations in sentence structure through the concept of Taqdīm and Ta'khīr. However, the systematic thought of contemporary scholars such as Dr. Fāḍil al-Sāmarā'ī on this concept remains underexplored. This study aims to reconstruct al-Sāmarā'ī's conceptual framework and compare it with classical balaghah views. A qualitative descriptive method with comparative concept analysis was employed through library research, using thematic analysis on primary sources including al-Sāmarā'ī's works and classical balaghah texts. The findings reveal that al-Sāmarā'ī systematizes Taqdīm-Ta'khīr into two classifications: (1) prioritizing a word over its 'āmil to indicate specification (ikhtiṣāṣ), and (2) prioritizing one word over another without 'āmil influence based on contextual demands. He rejects the circular classical explanation of